Agile Leadership's Influence on Lecturer Effectiveness and Career Development in the Education Sector - Joko Nugroho; Muniroh Muniroh; Antoni Ludfi Arifin (AL-ISHLAH: Jurnal Pendidikan, 2024)
Agile leadership, characterized by adaptability, responsiveness, and collaborative decision-making, has become prominent across industries, but its impact within the educational sector, particularly on lecturers' effectiveness and career development, remains underexplored. This study aims to systematically review the literature on how agile leadership influences these areas within the education sector. A systematic literature review was conducted using databases such as Google Scholar, PubMed, and Web of Science. Following the PRISMA guidelines, 25 peer-reviewed articles published between 2013 and 2023 were selected based on inclusion and exclusion criteria, focusing on agile leadership in education. Both qualitative and quantitative studies were included to ensure a comprehensive analysis. Key findings suggest a positive correlation between agile leadership and lecturer effectiveness, enhancing adaptability and innovation in teaching. Agile leadership also promotes career development by fostering continuous professional growth. However, challenges such as limited institutional support and insufficient leadership training hinder widespread adoption of agile leadership practices in education. The review indicates that agile leadership has the potential to reshape academic leadership models, improving teaching quality and lecturer career trajectories. Nonetheless, further research is needed to investigate long-term impacts and practical applications, particularly in diverse educational settings. Agile leadership positively influences lecturer effectiveness and career development, but institutional challenges must be addressed to fully realize its benefits. Future studies should explore more practical and sustainable implementations in educational contexts.